2018
DOI: 10.1590/0074-02760180323
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing reveals the co-existence of two transmission cycles of American cutaneous leishmaniasis in the Andean Region of Venezuela with Lutzomyia migonei as the vector

Abstract: BACKGROUND The transmission routes for American cutaneous leishmaniasis (ACL) are in flux, so studies examining its transmission in humans, mammalian hosts, and sand fly vectors are urgently needed. OBJECTIVES The aim of this work was understand the epidemiological cycles of Leishmania spp., which causes ACL in the Andean Region of Venezuela, by identifying the Leishmania and the sand fly species involved in human and dog infections. METHODS Thirty-one biopsies from patients in Mérida and Táchira states with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…migonei (França) is an important vector of Leishmania (Viannia) braziliensis, and one of the causative agents of cutaneous leishmaniasis in South America, especially in Brazil [17][18][19]. Torrellas et al [20] found Mg. migonei infected with Le. (V.) guyanensis and Le.…”
Section: Introductionmentioning
confidence: 99%
“…migonei (França) is an important vector of Leishmania (Viannia) braziliensis, and one of the causative agents of cutaneous leishmaniasis in South America, especially in Brazil [17][18][19]. Torrellas et al [20] found Mg. migonei infected with Le. (V.) guyanensis and Le.…”
Section: Introductionmentioning
confidence: 99%
“…In western Venezuela, it was described as anthropophilic adapted to both humid and dry mountain forests with wide altitudinal distribution (Chaves and Añez 2004), and was incriminated as vector in two epidemiological cycles, involving L. mexicana Biagi 1953 and L. guyanensis Floch 1954 (TL etiological agents) (Torrellas et al 2018). In northeastern Brazil, Mg. migonei was found in high abundance in remote indigenous villages in a semiarid region associated with transmission cycles of L. braziliensis Vianna 1911 (TL agent) (Sales et al 2019) and also in the Atlantic coast adapted to indoor environment suspected to be involved in L. infantum (VL agent) transmission (Silva et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…reported in dogs in the Americas, with their proven or suspected animal reservoirs and sand fly vectors Leishmania spp. Proven or suspected wild reservoirs a Proven or suspected vectors b Geographical distribution (in dogs) L. amazonensis Several species of small rodents, opossums, and other wildlife Bichromomyia flaviscutellata , Bichromomyia olmeca olmeca , and Pintomyia nuneztovari Brazil [ 43 , 44 ] and Colombia [ 15 , 92 ] L. braziliensis Several species of small rodents, opossums, and other wildlife Nyssomyia intermedia , Nyssomyia neivai , Nyssomyia whitmani , Migonemyia migonei , Psychodopygus complexus , Psychodopygus davisi , and Psychodopygus wellcomei Argentina [ 93 ], Bolivia [ 94 ], Brazil [ 95 ], Colombia [ 15 , 45 ], Mexico [ 96 ], Panama [ 13 ], Paraguay [ 97 ] c , Peru [ 65 ], and Venezuela [ 98 ] L. guyanensis Linnaeus’s two-toed sloth ( Choloepus didactylus ), southern tamandua ( Tamandua tetradactyla ), and other wildlife Nyssomyia anduzei and Nyssomyia umbratilis Brazil [ 17 ], Colombia [ 14 ] and Venezuela [ 99 ] L. infantum Several species of carnivores (mainly canids), rodents, opossums, monkeys, and other wildlife Lutzomyia cruzi , Lutzomyia longipalpis , Migonemyia migonei , Pintomyia evansi , and Psathyromyia shannoni Argentina [ 100 ], Bolivia [ 94 ], Brazil [ 101 ], Canada [ …”
Section: Etiology Of Canine Leishmaniasis In the Americasmentioning
confidence: 99%